Vortex states in soft magnets in two and three dimensions - COEY, JOHN MICHAEL DAVID; DIAO, ZHU; VENKATESAN, MUNUSWAMY (My University, 2010)
The magnetization curves of arrays of near-spherical soft ferromagnetic particles are compared with those of quasi-two-dimensional dots with similar radius prepared by a rapid e-beam lithographic technique. Curves for the three-dimensional particles are anhysteretic and fit a M(H)/Ms=tanh(c?0H) law, whereas the two-dimensional arrays show irreversible segments in the first and third quadrants where the planar vortex state transforms to a collinear state by discontinuous rotation of magnetization about an axis perpendicular to the vortex axis. The additional symmetry of the spherical particle allows this rotation to occur continuously, without energy barriers due to the demagnetizing field.
PUBLISHED
Keywords: Micromagnetics; Magnetization reversal; Nanodot array; e-beam lithography